PERAN SHADOW TEACHER DALAM PEMBELAJARAN IPA KELAS IV DI SEKOLAH ALAM INKLUSI JOGJA GREEN SCHOOL - Heni Raehani; Anita Ekantini; Nimas Asri Handayani; Siti Muthia Azzahra; Dania Cucu Rizkiyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Inclusive education provides equal learning opportunities for all students, including those with special needs (ABK). Science learning involves abstract concepts and requires logical thinking skills, thus necessitating the support of a shadow teacher. This study aims to analyze the role of shadow teachers in fourth-grade science learning at Sekolah Alam Inklusi Jogja Green School. This study employs a qualitative approach using the case study method. The research subjects consisted of one shadow teacher, one classroom teacher, and one student with special needs. Data were collected through semi-structured interviews and observations, then analyzed using the Miles, Huberman, and Saldana interactive model through data condensation, data presentation, and conclusion drawing and verification. The results of the study indicate that the shadow teacher plays a role in support strategies through dual attention and repeated explanations, hands-on learning and natural environment-based learning, strengthening inclusive social interactions, and an assessment system through support in understanding assessment instructions and remedial follow-up tailored to the needs of students with special needs. Thus, the shadow teacher plays a role in the academic, social, and learning development aspects of students with special needs at the inclusive nature school.